2017
DOI: 10.1002/ep.12784
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the oxic‐settling‐anaerobic (OSA) process into an anoxic–oxic system for sewage sludge reduction and nutrient removal

Abstract: The production of sludge in biological wastewater treatments is a growing problem worldwide as it entails economic, environmental, and health problems. The oxic‐settling‐anaerobic (OSA) process is one of the techniques that have been developed to reduce the sludge produced in the activated sludge process (ASP). This article reports the feasibility of the application of the OSA process in a nutrient removal system, specifically, in an anoxic–oxic (A) process. The results reveal TN removal in the A + OSA system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Compared with the available studies carried out with real wastewater on WWTP configured according to BNR schemes (Coma et al, 2015;Romero Pareja et al, 2018;Nikpour et al, 2020;Ferrentino et al, 2021), the results of the present study indicated that the excess sludge reduction was higher when implementing the scheme B. Thus, a double-growth limitation strategy consisting in a prolonged substrate limitation after a sufficient long retention under anaerobic condition, allowed obtaining a higher excess sludge minimization.…”
Section: Performances Of Excess Sludge Reductioncontrasting
confidence: 64%
“…Compared with the available studies carried out with real wastewater on WWTP configured according to BNR schemes (Coma et al, 2015;Romero Pareja et al, 2018;Nikpour et al, 2020;Ferrentino et al, 2021), the results of the present study indicated that the excess sludge reduction was higher when implementing the scheme B. Thus, a double-growth limitation strategy consisting in a prolonged substrate limitation after a sufficient long retention under anaerobic condition, allowed obtaining a higher excess sludge minimization.…”
Section: Performances Of Excess Sludge Reductioncontrasting
confidence: 64%
“…In the literature, reports on the effect of OSA-like processes on sludge settleability are often controversial, as SVI value have been reported to both improve or worsen after OSA implementation. 4,[32][33][34] For instance, the studies by Corsino et al 4 and Pareja et al 35 report a reduction in SVI values up to 73% after implementing a CAS with the OSA process operated with a HRT SSR between 7 and 12 h. In contrast, under similar HRT SSR (3-9 h), Corsino et al 17 and Torregrossa et al 32 observed an increase in SVI value up to 77%. Furthermore, these results do not allow for a clear deduction regarding the impact of the system scale (pilot-or laboratory-scale) and influent type (synthetic or real wastewater) on sludge settleability, as a different combination of these operating conditions can be found in the studies aforementioned.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the proliferation of PAO has a positive impact on sludge settleability, as these bacteria tend to aggregate in dense clusters which contribute to preserving good settling properties for the sludge. 35…”
Section: Resultsmentioning
confidence: 99%
“…The pilot plant was equipped with pH, ORP, temperature, and dissolved oxygen (DO) probes and a programmable logic controller (PLC). Although DO concentration in the activated sludge process (aerobic reactor) is usually set at 2 mg/L, in the present work, a higher concentration was selected based on previous studies on OSA process [4,[8][9][10], which reported a wide range of DO concentrations, ranging from 2 to 7 mg O 2 /L. The DO set-point concentration into the aerobic tank of this study was 4.0 mg O 2 /L, providing also the mixing of the aerobic reactor.…”
Section: Osa Pilot Plant Operationmentioning
confidence: 99%
“…In recent years, the combination of the OSA process with other technologies capable of sludge volume reduction, such as thermal and mechanical treatment, was also studied [7,8]. Although the implementation of an additional tank in the return sludge line increases the investment cost, OSA process is an environmental-friendly technology with several advantages: (i) the proven excess sludge reduction [1,4,9,10], (ii) the process stability, and (iii) the easy implementation in current conventional activated sludge system (CAS) associated to low operational costs [3,11].…”
Section: Introductionmentioning
confidence: 99%